Correlation of Structural and Macroscopic Properties of Starches with Their Tabletability Using the SM2 Approach. Issue 11 (November 2015) - Dave, Vivek S.; Chanda, Monica; Sayles, Matt; Popielarczyk, Michael; Boyce, Heather; Bompelliwar, Sai Krishna; Bates, Simon; Morris, Ken R.; Haware, Rahul V.
ABSTRACT: The effects of PURE-DENT® and SPRESS® starch properties on their compression behavior was characterized using "SM 2 " approach (structural properties, macroscopic properties, and multivariate analysis). Moisture sorption rate constants, moisture content, amylose and amylopectin degradation enthalpy, percent crystallinity, amylose–amylopectin ratio, and cross-linking degree were used to profile starch structural properties. Particle density, particle size distribution, and Heckel compression descriptors [yield pressure (YP) of plastic deformation, and elastic recovery] were used as macroscopic descriptors. The structural and macroscopic properties were correlated qualitatively [principal component analysis (PCA)] and quantitatively [standard least square regression (SLSR)] with the tablet mechanical strength (TMS). These analyses revealed that the differences correlated with amylose–amylopectin content, particle density, compression mechanisms, and TMS between the starch grades. Univariate analysis proved lacking; however, PCA identified the particle size, moisture content, percent crystallinity, amylose–amylopectin ratio, and YP of plastic deformation and elastic recovery as the main factors influencing the starch TMS. SLSR quantified the positive influence of Fourier transform infrared spectra absorbance ratio at 1022–1003 and YP of the immediate elastic recovery, and the negative contribution of amylopectin content on the TMS. Therefore, starch amylose and amylopectin content, crystallinity, and lower elastic recovery are mainly responsible for better TMS.